2019
DOI: 10.1080/09168451.2019.1591263
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed Lactobacillus helveticus strain MCC1848 confers resilience to anxiety or depression-like symptoms caused by subchronic social defeat stress in mice

Abstract: The gut microbiota is involved in the pathogenesis of stress-related disorders. Probiotics can benefit the central nervous system via the microbiota–gut–brain axis, which raises the possibility that probiotics are effective in managing depression. In the present study, we examined the effects of heat-killed Lactobacillus helveticus strain MCC1848 in subchronic and mild social defeat stress (sCSDS) model mice (a widely used animal model of depression). MCC1848 supplementation significantly enhanced the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 41 publications
2
33
1
3
Order By: Relevance
“…Therefore, it can be speculated that L. helveticus influences the central 5-HT circuitry via the neural route. This is supported by a recent study showing that L. helveticus intake increased expression of 5-HT 1A receptors in the nucleus accumbens while restoring behaviors of depressed mice (Maehata et al, 2019).…”
Section: Microbial Ne Central Ne System and Hpa Axissupporting
confidence: 66%
See 2 more Smart Citations
“…Therefore, it can be speculated that L. helveticus influences the central 5-HT circuitry via the neural route. This is supported by a recent study showing that L. helveticus intake increased expression of 5-HT 1A receptors in the nucleus accumbens while restoring behaviors of depressed mice (Maehata et al, 2019).…”
Section: Microbial Ne Central Ne System and Hpa Axissupporting
confidence: 66%
“…Lactobacillus helveticus intake enabled the recovery of chronicand subchronic-stressed rodents from their state of depression (Liang et al, 2015;Maehata et al, 2019). Probiotic sticks containing L. helveticus, in addition to Bifidobacterium longum, reduced clinical depression and depressive-like symptoms in MDD patients (Kazemi et al, 2019) and healthy individuals (Messaoudi et al, 2011), respectively.…”
Section: Lactobacillus Helveticusmentioning
confidence: 99%
See 1 more Smart Citation
“…Some probiotics, known as brain probiotics, produce gamma-aminobutyric acid and serotonin [3,4]. Some heat-killed lactobacilli alter microbiota composition [5] and affect the host's neurological and psychiatric functions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies employing experimental animals have shown that administering specific probiotics eases stress-induced glucocorticoid and inflammatory cytokine responses in conjunction with decrease in depression-and anxiety-related behaviors (4,7,15). Dietary supplements of Lactobacillus have been found to increase psychosocial stress resilience in sCSDS mice (23) and gene expression of neurotrophic factors such as brain-derived neurotrophic factor (BDNF) in the hippocampus (38). Moreover, patients with major depression were found to have lower Bifidobacterium and Lactobacillus counts in their gut than healthy controls did (1).…”
mentioning
confidence: 99%